Consumer preference and acceptance of two Colombian sweet milks: results of a consumer survey (UGCiencia, 2015)
The degree of sensory preference and acceptance of two typical Colombian sweet milk products (Arequipe and Manjar Blanco) were evaluated. Two kinds of tests - preference and acceptance - (Seven-point Hedonic Test) were applied. The judging panel consisted of 76 untrained consumers from Cali. The analyses of the data were done using two statistical tests (Friedman and Wilcoxon). We found that flavor was the sensory parameter that obtained the highest ranking and consumers preferred Arequipe more than Manjar Blanco.